Tamsulosin: An unthinkable cause of priapism - Anurag Mishra; Atanu Jana (Annals of Medical Science and Research)
Priapism is the full or partial erection that continues for more than 4 h beyond sexual stimulation and orgasm or is unrelated to sexual stimulations. Most commonly, it is idiopathic in nature. Few drugs are also associated with priapism. Here, we are presenting a case report of tamsulosin-associated priapism in 36-year-old men.